Development of Vaginal Pseudoaneurysm 3 Years after Cesarean Section Possibly Induced by Anticoagulant and Antiplatelet Therapies - Yui Kinjo; Tadatsugu Kinjo; Keiko Mekaru; Hayase Nitta; Hitoshi Masamoto; Yoichi Aoki (Case Reports in Obstetrics and Gynecology)
Pseudoaneurysms generally develop when an arterial puncture site is inadequately sealed. We encountered a case of vaginal pseudoaneurysm that developed 3 years after cesarean section in a 35-year-old gravida 7 para 4 woman who was prescribed with anticoagulant and antiplatelet drugs after surgeries for ventricular septal defect and aortic valve replacement. Pelvic computed tomography scan revealed a large mass, which showed a dappled contrast filling on the arterial phase, located in the posterior vaginal wall. The vaginal pseudoaneurysm was completely occluded by embolization of the left vaginal artery. Anticoagulation and antiplatelet therapies can be potential causes of spontaneous pseudoaneurysm rupture. Extrauterine pseudoaneurysm has a long period of time between cesarean section and pseudoaneurysm discovery. Considering that pseudoaneurysm shows different clinical features for each patient, we should always consider pseudoaneurysm when we assess a patient with postpartum hemorrhage.